Pengaruh Green Accounting, Environmental Performance, Dan Carbon Emission Disclosure Terhadap Profitabilitas (Studi Empiris Pada Perusahaan Sektor Energi Yang Terdaftar Pada Bursa Efek Indonesia Tahun 2020-2024) - Al-Idris, Mohamad Yudha; Mansur, Fitrini; Hernando, Riski (Jurnal Akuntansi & Keuangan Unja, 2025)
This study aims to analyze the effect of Green Accounting, Environmental Performance, and Carbon Emission Disclosure on company profitability, with Return on Equity (ROE) as the profitability indicator. The research sample consists Energy sector company listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The data used in this study is secondary data obtained from the companies' annual reports. The analytical method employed is multiple regression analysis. The results show that Green Accounting has a significant negative effect on company profitability, while Environmental Performance and Carbon Emission Disclosure have no significant effect on profitability. These findings indicate that companies implementing Green Accounting practices tend to experience a decline in profitability, and vice versa. Meanwhile, good Environmental Performance and Carbon Emission Disclosure do not significantly impact profitability. This study provides important contributions for company management and stakeholders in understanding the impact of environmental costs on profitability and offers insights for strategic decision-making related to environmental investments.